Extensive morphea profunda with autoantibodies and benign tumors: A rare case report - Leelavathy Budamakuntla; Dipali Malvankar (Indian Dermatology Online Journal, 2012)
The term deep morphea describes a variant of morphea (localised scleroderma) in which inflammation and sclerosis are found in the deep dermis, panniculus, fascia or superficial muscle. It is sometimes associated with autoantibodies. We report the case of a 49 year-old male who had morphea profunda (radiologically and histopathologically confirmed) affecting mainly the left side of the body with face, trunk and limb involvement, along with autoantibody production and associated neurofibromas and lipomas.